1999
DOI: 10.1115/1.1302296
|View full text |Cite
|
Sign up to set email alerts
|

1999 Turbomachinery Committee Best Paper Award: Development of Advanced Compressor Airfoils for Heavy-Duty Gas Turbines— Part I: Design and Optimization

Abstract: A new family of subsonic compressor airfoils, which are characterized by low losses and wide operating ranges, has been designed for use in heavy-duty gas turbines. In particular the influence of the higher airfoil Reynolds numbers compared to aeroengine compressors and the impact of these differences on the location of transition are taken into account. The design process itself is carried out by the combination of a geometric code for the airfoil description, with a blade-to-blade solver and a numerical opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…With shock-free and controlled diffusion features, controlled-diffusion airfoil (CDA) introduced in the early 1980s was originally designed for supercritical cascades (Dunker et al, 1984;Niederdrenk et al, 1987;Elazar and Shreeve, 1990;Steinert et al, 1991;Jiang et al, 2015). As CDA blades were primarily developed for aero-engines but not the optimum solution for heavy-duty gas turbines, Köller et al (2000) and Kusters et al (2000) designed a high subsonic compressor airfoil family (Ma ≤ 0.8, θ≤ 30 °, e/b 25%). The optimization results demonstrated that the well-controlled front loading airfoil obtained good performance through promoting early transition without strong laminar separation.…”
Section: Introductionmentioning
confidence: 99%
“…With shock-free and controlled diffusion features, controlled-diffusion airfoil (CDA) introduced in the early 1980s was originally designed for supercritical cascades (Dunker et al, 1984;Niederdrenk et al, 1987;Elazar and Shreeve, 1990;Steinert et al, 1991;Jiang et al, 2015). As CDA blades were primarily developed for aero-engines but not the optimum solution for heavy-duty gas turbines, Köller et al (2000) and Kusters et al (2000) designed a high subsonic compressor airfoil family (Ma ≤ 0.8, θ≤ 30 °, e/b 25%). The optimization results demonstrated that the well-controlled front loading airfoil obtained good performance through promoting early transition without strong laminar separation.…”
Section: Introductionmentioning
confidence: 99%
“…In direct design method, optimum geometry is achieved by evaluation of secondary aerodynamic properties such as profile loss. Koller et al (2000) and Kusters et al (2000) applied this method to generate new developed sections for axial flow compressors in subsonic regimes. They found that the Reynolds number and turbulence intensity can change the shape of airfoil by means of minimum loss value and maximum operating range.…”
Section: Introductionmentioning
confidence: 99%
“…The compressor consists of different types of airfoils along the stages: special airfoil designs in the front, multi-circular arc thickness distributions in the mid and NACA 65 thickness distributions in the rear. In the 90s numerical optimization emerged in compressor design: Köller et al (2000) employed direct numerical optimization in combination with the blade-to-blade flow solver MISES to generate a set of optimal airfoil geometries for systematically varying cascade properties. At component level, early work conducting throughflow design optimization includes the studies of Oyama and Liou (2002).…”
Section: Introductionmentioning
confidence: 99%
“…At component level, early work conducting throughflow design optimization includes the studies of Oyama and Liou (2002). Blade-to-blade optimized airfoil sections with a strategy similar to Köller et al (2000) have been applied to the mid stages of an industrial compressor in (Sieverding et al, 2004). The new blade designs have been evaluated with 3D CFD and measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation